VD_FINDINFO Décision / 2014 / 919 vom 11. August 2014 - VD Tribunal cantonal (2014)
NON-LIEU, FRAIS DE LA PROCÉDURE, MAÎTRISE DU VÉHICULE | 31 al. 1 LCR, 382 al. 1 CPP (CH), 395 let. b CPP (CH), 426 al. 2 CPP (CH)